2018
DOI: 10.1016/j.ccell.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

NRL and CRX Define Photoreceptor Identity and Reveal Subgroup-Specific Dependencies in Medulloblastoma

Abstract: Cancer cells often express differentiation programs unrelated to their tissue of origin, although the contribution of these aberrant phenotypes to malignancy is poorly understood. An aggressive subgroup of medulloblastoma, a malignant pediatric brain tumor of the cerebellum, expresses a photoreceptor differentiation program normally expressed in the retina. We establish that two photoreceptor-specific transcription factors, NRL and CRX, are master regulators of this program and are required for tumor maintenan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 44 publications
8
55
0
Order By: Relevance
“…In contrast, MYC expression showed an opposite expression pattern as compared to INHBB (Fig D): Group 3γ subtype, which is characterized by an enrichment of MYC amplifications, displayed the highest MYC expression levels, whereas the α subtype showed the lowest (Cavalli et al , ). We recently reported that NRL and CRX control photoreceptor genes expression and define a subset of Group 3 tumors (Garancher et al , ). We found that alike INHBB, NRL is highly expressed in the G3α subtype (Fig D and ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, MYC expression showed an opposite expression pattern as compared to INHBB (Fig D): Group 3γ subtype, which is characterized by an enrichment of MYC amplifications, displayed the highest MYC expression levels, whereas the α subtype showed the lowest (Cavalli et al , ). We recently reported that NRL and CRX control photoreceptor genes expression and define a subset of Group 3 tumors (Garancher et al , ). We found that alike INHBB, NRL is highly expressed in the G3α subtype (Fig D and ).…”
Section: Resultsmentioning
confidence: 99%
“…This subtype displays high photoreceptor gene expression (Cavalli et al , ), including those of the two master regulators of this program, NRL and CRX. Accordingly, we recently showed that their expression defines a specific subtype within Group 3 (Garancher et al , ). Our data may suggest that the expression of INHBB could lead to Smad2/3 activation in this subtype.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations